ANALISIS GERAK TARI NAMPI’ SEAK DALAM UPACARA ADAT NAIK DANGO PADA MASYARAKAT DAYAK KANAYATN - Evin, Stepani Devia; Istiandini, Winda; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe background of this research is based on the lack of interest of the community in the present in processing the rice traditionally because of technological progress so slowly. People begin to forget the existing tradition, one of the traditions in processing rice in Dayak Kanayatn community is Nampi' Seak or winnowing rice, where at traditional ceremony Naik Dango, Nampi' Seak tradition is shown in the form of dance of the race by developing basic movements in the process of winnowing rice. The purpose of this study is to examine the core motion structure of Nampi' Seak dance, so that when working on the dance for the race does not reduce or eliminate the core movements that are in it. The method used is descriptive method with qualitative form through ethnocoreology approach. Research data is the result of observation, interview, and documentation. From the result of this research, there are 5 core motion sentences within 1 dance cluster of Nampi' Seak that is Ngentak motion, Nampi motion', Ngaruman motion, Totokng motion, and Napok Nyiruk motion. The notation of Nampi? Seak dance structure using Laban notation by using the symbol in the motion of dance. The resulting contribution is in the form of VCD video tutorials in which discuss about Nampi' Seak dance motion tutorial delivered by tutor and video of Nampi' Seak dance performances based on the motion and pattern of floor that have been developed. Keywords: dance motion, Nampi' Seak, Naik Dango